Early immune response to Toxoplasma gondii lineage III isolates of different virulence phenotype - Uzelac, Aleksandra; Klun, Ivana; Djurković-Djaković, Olgica (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Toxoplasma gondii is an intracellular parasite of importance to human and veterinary health. The structure and diversity of the genotype population of T. gondii varies considerably with respect to geography, but three lineages, type I, II and III, are distributed globally. Lineage III genotypes are the least well characterized in terms of biology, host immunity and virulence. Once a host is infected with T.gondii, innate immune mechanisms are engaged to reduce the parasite burden in tissues and create a pro-inflammatory environment in which the TH1 response develops to ensure survival. This study investigated the early cellular immune response of Swiss-Webster mice post intraperitoneal infection with 10 tachyzoites of four distinct non-clonal genotypes of lineage III and a local isolate of ToxoDB#1. The virulence phenotype, cumulative mortality (CM) and allele profiles of ROP5, ROP16, ROP18 and GRA15 were published previously. Methods Parasite dissemination in different tissues was analyzed by real-time PCR and relative expression levels of IFNγ, IL12-p40, IL-10 and TBX21 in the cervical lymph nodes (CLN), brain and spleen were calculated using the ΔΔCt method. Stage conversion was determined by detection of the BAG1 transcript in the brain. Results Tissue dissemination depends on the virulence phenotype but not CM, while the TBX21 and cytokine levels and kinetics correlate better with CM than virulence phenotype. The earliest detection of BAG1 was seven days post infection. Only infection with the genotype of high CM (69.4%) was associated with high T-bet levels in the CLN 24 h and high systemic IFNγ expression which was sustained over the first week, while infection with genotypes of lower CM (38.8%, 10.7% and 6.8%) is characterized by down-regulation and/or low systemic levels of IFNγ. The response intensity, as assessed by cytokine levels, to the genotype of high CM wanes over time, while it increases gradually to genotypes of lower CM. Discussion The results point to the conclusion that the immune response is not correlated with the virulence phenotype and/or allele profile, but an early onset, intense pro-inflammatory response is characteristic of genotypes with high CM. Additionally, high IFNγ level in the brain may hamper stage conversion.